Pengembangan Aplikasi Sistem Basis Data Penjualan, Pembelian, dan Persediaan: Studi Kasus Pada PT. Speed Game - Honni, Honni; Marcelino, Ryan Ferdy; Radjali, Yohanes (Bina Nusantara University, 2011)
This study aims to to perform database application development system on purchasing, sales and inventory of PT. Speed Game, a company that applies manual database system. The company often faces difficulties in obtaining and processing data information about purchasing, sales and inventory that may affect the employee performance. Therefore, to facilitate the company in processing data and produce information quickly, precisely and accurately, a development of database application system is build using database lifecycle method. The result achieved is a database application system of purchasing, sales and inventory that will facilitate the company in running its business processes. It can be concluded that the development of database application system is necessary to help the company accelerate and simplify the obtaining information process and as well as store and retrieve any information needed.